2020
DOI: 10.1002/14651858.cd008294.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Pine bark (Pinus spp.) extract for treating chronic disorders

Abstract: Pine bark (Pinus spp.) extract for treating chronic disorders (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 109 publications
(70 reference statements)
0
9
0
1
Order By: Relevance
“…Several in vitro, animal and human studies have indicated the prophylactic and therapeutic effects of extracts from various pine species [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. In a systematic review, published by the Cochrane Collaboration, which included 27 RCTs evaluating the effects of supplements containing pine bark extracts on 10 different chronic diseases: asthma, Attention Deficit Hyperactivity Disorder, cardiovascular disease and risk factors, chronic venous insufficiency, diabetes, erectile dysfunction, female sexual dysfunction, osteoarthritis, osteopenia and traumatic brain injury, it was concluded that small sample sizes, a limited number of RCTs, variability in outcome measures and poor reporting of the RCTs included, rendered it impossible to draw definitive conclusions about the efficacy or safety of supplements containing pine bark extract [ 108 ]. However, the aforementioned review did not take into account many other studies, including particularly interesting research on skin health and protection.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Several in vitro, animal and human studies have indicated the prophylactic and therapeutic effects of extracts from various pine species [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. In a systematic review, published by the Cochrane Collaboration, which included 27 RCTs evaluating the effects of supplements containing pine bark extracts on 10 different chronic diseases: asthma, Attention Deficit Hyperactivity Disorder, cardiovascular disease and risk factors, chronic venous insufficiency, diabetes, erectile dysfunction, female sexual dysfunction, osteoarthritis, osteopenia and traumatic brain injury, it was concluded that small sample sizes, a limited number of RCTs, variability in outcome measures and poor reporting of the RCTs included, rendered it impossible to draw definitive conclusions about the efficacy or safety of supplements containing pine bark extract [ 108 ]. However, the aforementioned review did not take into account many other studies, including particularly interesting research on skin health and protection.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Nonetheless, the use of Pycnogenol® (100 mg/day), for 3 to 8 weeks prior to the birch pollen season, did not lead to significant improvement in nasal and ocular symptoms [ 31 ]. French maritime pine bark extract supplementation has already been studied under other pathophysiological conditions, as traumatic brain injury [ 45 ], urinary tract infections [ 46 ], osteoarthritis [ 47 ], among others [ 48 ] with different doses and duration, besides impact on clinical outcomes. The methodological limitations and imprecision lead to a low evidence level for this outcome, as can be seen in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The present study did not investigate the potential active ingredient(s) of PBE. However, accumulating data indicate that maritime pine bark extract contains high levels of procyanidins and proanthocyanidins ( 18 , 53 , 54 ). Based on previous studies, the bark extract of Pinus thunbergii , which is a Korean maritime pine, may also contain procyanidins and proanthocyanidins.…”
Section: Discussionmentioning
confidence: 99%